Is COVID-19 to blame?: Trends of incidence and sex ratio in youth-onset type 2 diabetes in Germany - Denzer, Christian; Rosenbauer, Joachim; Klose, Daniela; Körner, Antje; Reinehr, Thomas; Baechle, Christina; Schröder, Carmen; Wiegand, Susanna; Holl, Reinhard W.; Prinz, Nicole (Diabetes care, 2023)
We investigated the incidence of pediatric type 2 diabetes (T2D) in Germany during 2 years of the coronavirus disease 2019 (COVID-19) pandemic (2020-2021) compared with the control period 2011-2019.Data on T2D in children (aged 6 to <18 years) were obtained from the DPV (German Diabetes Prospective Follow-up) Registry. Poisson regression was used to estimate incidences for 2020 and 2021 based on data from 2011 to 2019, and these were compared with observed incidences in 2020 and 2021 by estimating incidence rate ratios (IRRs) with 95% CIs.Incidence of youth-onset T2D increased from 0.75 per 100,000 patient-years (PYs) in 2011 (95% CI 0.58, 0.93) to 1.25 per 100,000 PYs in 2019 (95% CI 1.02, 1.48), an annual increase of 6.8% (95% CI 4.1, 9.6). In 2020, T2D incidence increased to 1.49 per 100,000 PYs (95% CI 1.23, 1.81), which was not significantly higher than predicted (IRR 1.15; 95% CI 0.90, 1.48). In 2021, the observed incidence was significantly higher than expected (1.95; 95% CI 1.65, 2.31 vs. 1.38; 95% CI 1.13, 1.69 per 100,000 PYs; IRR 1.41; 95% CI 1.12, 1.77). Although there was no significant increase in incidence in girls in 2021, the observed incidence in boys (2.16; 95% CI 1.73, 2.70 per 100,000 PYs) significantly exceeded the predicted rate (IRR 1.55; 95% CI 1.14, 2.12), leading to a reversal of the sex ratio of pediatric T2D incidence.In Germany, incidence of pediatric T2D increased significantly in 2021. Adolescent boys were more affected by this increase, resulting in a reversal of the sex ratio of youth-onset T2D.
Online veröffentlicht: 4. Mai 2023
Gesehen am 07.12.2023